1999
DOI: 10.1080/0141192990250103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Patterns of Teacher Interaction in Primary Classrooms: 1976‐96

Abstract: For the past two decades there has been persistent controversy regarding the effectiveness of the different teaching methods used in the English primary classroom. One of the earliest studies of the primary classroom, the ORACLE study, described the typical behaviours of teachers and pupils. Since that time there have been various interventions designed ‘to change the way that primary teachers teach’. The research reported here evaluates the success of these interventions by replicating the work of 20 years ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 13 publications
4
51
0
13
Order By: Relevance
“…That's what I am looking for", "You see you've discovered a couple of things that the author figuratively implies and only smart readers could understand". Galton et al (1999) and Mercer et al (1999) claim that the use of such language is important for learning because it enables ways of scaffolding dialogues so that students learn to engage with others on the issues at hand. By contrast, the teachers' verbal behaviours involved fewer controlling and disciplining verbal behaviours (18 in Phase 2 compared to 28 in Phase 1 and 12 in Phase 2 compared to 15 in Phase 1, respectively).…”
Section: Changes On the Teachers' Sidementioning
confidence: 99%
“…That's what I am looking for", "You see you've discovered a couple of things that the author figuratively implies and only smart readers could understand". Galton et al (1999) and Mercer et al (1999) claim that the use of such language is important for learning because it enables ways of scaffolding dialogues so that students learn to engage with others on the issues at hand. By contrast, the teachers' verbal behaviours involved fewer controlling and disciplining verbal behaviours (18 in Phase 2 compared to 28 in Phase 1 and 12 in Phase 2 compared to 15 in Phase 1, respectively).…”
Section: Changes On the Teachers' Sidementioning
confidence: 99%
“…One of the earliest studies, the ORACLE project (Observational Research and Classroom Learning Evaluation) conducted from 1976-1978 in 58 classrooms in the UK found that with an average of 35 students in a classroom, teachers spent under 5 seconds with children in 40% of one-to-one exchanges (Galton, Hargreaves, Comber, Wall, & Pell, 1999, p. 23). Twenty years later, Galton et al (1999) replicated the ORACLE Project with 28 teachers to find that though there was a slight increase in the time spent on whole class teacher-pupil interactions (an increase of 16%), there was also an increase in time spent with small groups (7%) and less time spent with individual students (a decrease of 23.2%). An analysis of the dialogue evidenced in these classrooms found that the shift had resulted in an increased amount of time spent talking "at" students and not "with" students.…”
Section: Conferencingmentioning
confidence: 99%
“…Again in the UK, Galton, Hargreaves, Comber, Wall, and Pell (1999) carried out a detailed observational study of types of interaction in the classrooms of 28 teachers of students in their final year of primary school, in a repeat of a study carried out in 1976. In the 1976 study, across 58 classrooms, it was found that teachers, on average, engaged in around six minutes of individual interaction with each child per day.…”
Section: Generativitymentioning
confidence: 99%